Biological and clinical heterogeneity of MYCN-amplified medulloblastoma - Korshunov, Andrey; Remke, Marc; Kool, Marcel; Hielscher, Thomas; Witt, Hendrik; Benner, Axel; Deimling, Andreas von; Kulozik, Andreas; Westermann, Frank; Lichter, Peter; Pfister, Stefan (Acta neuropathologica, 2012)
Focal high-level amplifications of MYC (or MYCC) define a subset of high-risk medulloblastoma patients. However, the prognostic role of MYCN oncogene amplification remains unresolved. We aimed to evaluate the prognostic value of this alteration alone and in combination with biological modifiers in 67 pediatric medulloblastomas with MYCN amplification (MYCN-MB). Twenty-one MYCN-MB were examined using gene expression profiling and array-CGH, whereas for 46 tumors immunohistochemical analysis and FISH were performed. All 67 tumors were further subjected to mutational analyses. We compared molecular, clinical, and prognostic characteristics both within biological MYCN-MB groups and with non-amplified tumors. Transcriptomic analysis revealed SHH-driven tumorigenesis in a subset of MYCN-MBs indicating a biological dichotomy of MYCN-MB. Activation of SHH was accompanied by variant-specific cytogenetic aberrations including deletion of 9q in SHH tumors. Non-SHH MB were associated with gain of 7q and isochromosome 17q/17q gain. Among clinically relevant variables, SHH subtype and 10q loss for non-SHH tumors comprised the most powerful markers of favorable prognosis in MYCN-MB. In conclusion, we demonstrate considerable heterogeneity within MYCN-MB in terms of genetics, tumor biology, and clinical outcome. Thus, assessment of disease group and 10q copy-number status may improve risk stratification of this group and may delineate MYCN-MB with the same dismal prognosis as MYC amplified tumors. Furthermore, based on the enrichment of MYCN and GLI2 amplifications in SHH-driven medulloblastoma, amplification of these downstream signaling intermediates should be taken into account before a patient is enrolled into a clinical trial using a smoothened inhibitor.